Rochagem como alternativa para fornecimento de potássio para as culturas - Santos, Douglas da Silva (2013)
In order to evaluate the use of rock powder and rock thermally treated applied as an alternative source of potassium for crops, three studies were conducted: Incubation study, biological study and leaching study. All studies were conducted in a greenhouse, using samples of two types of soils, an Oxisol Red (LVd) and a Ustoxic Quartzipsamment (RQo). The first study, evaluated the release potassium to the soil. Six sources of potassium (phonolite, feldspar, nepheline, verdete, thermopotash and KCl) and two levels of potassium (200 and 400 kg ha-1). Potassium in the soil, was determined after incubation for 60 days. It was observed that phonolite was effective to release, together with the thermopotash while .The sources feldspar, verdete and nepheline are not . The second test evaluated leaching losses of potassium from granular potash, powder rocks phonolite and feldspar, in samples of LVd and RQo. Each sources of potassium was distributed into 20-cm diameter and 80-cm high leaching columns. At the end of the experiment potassium present in the leachate and in each ring of the column was determined. Phonolite and feldspar provided more potassium in the top soil layer (0-5cm). KCl provided more potassium in subsurface layers, showing greater mobility in the profile. The mobility of phonolite and feldspar were similar. For the biological study, done in pots, millet was grown two consecutive times to determine the absorption of potassium, and others nutrients, presents in rocks, phonolite, feldspar, nepheline, verdete, and thermally treated rock, thermopotash granulated (TK-GR) or powder (TK-Pó) at doses 100 and 200 kg of K2O ha-1 . At the end of the experiment dry matter, K+, Ca+ and Mg+ contents in ground millet matter, and accumulate in millet ground matter, K+ and Si soil were analyzed. For two consecutive crops, the agronomi efficiency of TK-Pó was greater than KCl in both soil samples, LVD and RQo. Millet absorbed potassium, calcium and magnesium, supplied by TK-Pó. The agronomy efficiency of TK-GR, verdete, feldspar, phonolite and nepheline were lower than KCl and TKPó both in LVd and RQo. In conclusion, only TK-Pó can be used as a potassium source in millet.